THE STUDY OF THE METHODOLOGICAL SYSTEM AND ISSUES RELATED TO THE TEACHING OF PHYSICS AND ASTROPHYSICS IN HIGHER EDUCATIONAL INSTITUTIONS - Abdurakibov, A.A; Rashidov, D.G; Nishanova, S.B; O‘tkirov, Sh.X (Innovative Development in Educational Activities, 2023)
Today, there are a number of problems related to the pedagogical point of view in teaching students, and in order to solve them, the article considers and studies possible methodological systems for use in teaching physics and astrophysics in universities.